Measurement of beauty photoproduction near threshold using di-electron events with the H1 detector at HERA - Aaron, Francisc Dionisie; Hennekemper, Eva; Krüger, Katja; Lendermann, Victor; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2012)
The cross section for ep→ebb¯Xep→ebb¯Xep → e\, b\bar{b} X in photoproduction is measured with the H1 detector at the ep-collider HERA. The decay channel bb¯→eeX′bb¯→eeX′b\bar{b} → ee X' is selected by identifying the semi-electronic decays of the b-quarks. The total production cross section is measured in the kinematic range given by the photon virtuality Q 2≤1 GeV2, the inelasticity 0.05≤y≤0.65 and the pseudorapidity of the b-quarks |η(b)|,|η(b¯)|≤2|η(b)|,|η(b¯)|≤2|η(b)|, |η(\bar{b})|≤2. The differential production cross section is measured as a function of the average transverse momentum of the beauty quarks 〈P T (b)〉 down to the threshold. The results are compared to next-to-leading-order QCD predictions.